Decolonising (through) inclusive education? - Walton, Elizabeth (Faculty of Education, Nelson Mandela Metropolitan University, 2018)
Inclusive education seeks to reduce exclusion from and within schools, and to secure participation and learning success for all. Its origins are in countries of the Global North, and countries of the Global South, like South Africa, have been relatively late to introduce inclusive education. Inclusive education has been critiqued as constituting a neocolonial project and an unwelcome imposition on countries of the Global South. It can be seen as a form of coloniality because the knowledge from Euro-American countries dominates the field. Furthermore, countries are expected to fund a model of inclusion developed in the resource-rich North, and current schooling perpetuates colonial hierarchies. Responding to this critique, this article presents an Afrocentric model of inclusive education, citing scholars who claim that inclusive education is congruent with traditional African culture and community and resonates with ubuntu. It is then shown that this argument is not unassailable. An alternative is that inclusive education might be harnessed to further the decolonial project, and that aspects of inclusive education can resist the coloniality of knowledge, of power, and of being. This position may also be problematic because it could represent what has been termed settler innocence. Finally, implications for research and teaching are suggested.